Wicked, incomplete, and uncertain: user support in the wild and the role of technical communication - Swarts, Jason, author; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
How to document technologies that may hybridize into forms that not even their designers would have anticipated, and offers insight into the evolving role of a technical writer in an age of increasing user reliance on YouTube tutorials, message boards, and other resources for guidance.--Provided by publisher.
The exigences and forms of technical communication -- Task shift: changes in the object of documentation -- Shifted tasks and shifted problems: the problem of wicked and tame problems -- Credibility and user interaction: the challenge of decentered expertise -- A survey of action-based proto-genres of help -- The role of technical communication.
Keywords: Technical writing; Technology -- Documentation; Communication of technical information